White space interpretation in Hermann Rorschach’s inkblot test: Ananalysis of two male examinees’ responses - Hunca-Bednarska, Anna (Current Problems of Psychiatry, 2025)
Introduction: There are numerous points of controversy over the psychological interpretation of the so-called S responses – namely, the interpretation of white space in the Rorschach test. The aim of my paper was to verify the position held by Charles P. Fonda, who claims that the meaning of S responses depends on the results of the test as a whole. Materials and methods: I have presented the responses of two young men and coded them according to the Comprehensive System developed by John E. Exner. I chose this way of processing data as the most precise, relatively well formalized, and detailed one. The two examinees gave an almost identical number of responses in the whole test and a similar number of S responses, similarly distributed across the cards of the test. Results: I assessed and compared the results of the two examinees in terms of the effectiveness of their cognitive processes, self-control ability, mental resources, social adjustment, and self-esteem. Finally, I looked closely at the contents of a few responses, as in my opinion they symbolically expressed the examinees’ basic problems. Discussion: I tried to avoid describing the examinees’ psyche in nosological terms and to focus on presenting the way in which they experienced the world, as well as on how this experience affected their behavior. Conclusions: I found that in Examinee 1 criticism towards other people may stem from an excessively idealistic attitude to the world and from the ensuing disappointments. Good cognitive functioning, resistance to stress, positive self-esteem, and the socialized emotional sphere make this man’s S responses a sign of creative engagement in the problems encountered rather than a sign of maladjustment. In the case of Examinee 2, S responses can be understood as defiance and a generalized attitude of negativism, which play the role of defense against the excessively complicated, not fully comprehensible, and inhospitable world; these responses may, in their turn, contribute to the intensification of problems and to an increase in maladjustment.